2021
DOI: 10.1007/s00520-021-06351-1
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcome measures obtained via E-Health tools ease the assessment burden and encourage patient participation in cancer care (PaCC Study)

Abstract: Patient-reported outcome measures obtained via E-Health tools ease the assessment burden and encourage patient participation in cancer care (PaCC Study) Background E-health based patient-reported outcome measures (PROMs) have the potential to automate early identification of both nutrition status and distress status in cancer patients while facilitating treatment and encouraging patient participation. This cross-sectional study assessed the acceptability, accuracy, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
9
1
Order By: Relevance
“…Positive correlation of Cancer e-Support Program usage duration with self-efficacy (r = 0.290, p = .03), social support (r = 0.320, p = .02), and quality of life (r = 0.273, p = .04) at 3 months. 2020, China [21] Secondary data analysis of the multicentre, singleblinded, RCT [18] Intervention group from RCT [18] Mobile nutritional aspects of care via the app was efficiently integrated in clinical routine [38].…”
Section: Discussionmentioning
confidence: 99%
“…Positive correlation of Cancer e-Support Program usage duration with self-efficacy (r = 0.290, p = .03), social support (r = 0.320, p = .02), and quality of life (r = 0.273, p = .04) at 3 months. 2020, China [21] Secondary data analysis of the multicentre, singleblinded, RCT [18] Intervention group from RCT [18] Mobile nutritional aspects of care via the app was efficiently integrated in clinical routine [38].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these patients should also get intensive support from the help of artificial intelligence or special coaching programs, for example. There is starting to be documented evidence for the effectiveness of these forms of intensive support [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it also suggests the effectiveness of the workflow to address symptoms scored 4 and above, including the alert, the notification for the primary oncology -129 including improved physical and emotional symptoms, suggesting that these findings were not an artefact of time. 3,7,12,15,27,28 Notably, previous data have shown that patients are receptive to this type of intervention, 9,10 with the exception for older patients who face some challenges with technology. 29 Interestingly, in the present study, age did not impact level of engagement (p = 0.847), nor did level of education, income, race, or distance between patients' home and the cancer center.…”
Section: Discussionmentioning
confidence: 99%
“…6 A host of benefits have been associated with such interventions, including increased patient engagement, more highly integrated care of symptoms in oncology care and more effective symptom management by the health care team. [7][8][9][10][11] In addition, these programs may enhance self-management and autonomy, improve care regardless of age, sex and stage of the disease, and facilitate access to supportive care. 7,[12][13][14][15][16] Further, the use of eHealth/ mHealth-based interventions may favor early access to supportive care, reduce the burden of symptoms, improve Health-Related Quality of Life (HR-QOL) and promote longer survival.…”
Section: Introductionmentioning
confidence: 99%